Vocabulary Word Instruction for Students Who Read Braille. (April 2016) - Savaiano, Mackenzie E.; Compton, Donald L.; Hatton, Deborah D.; Lloyd, Blair P.
The association made between the meaning, spelling, and pronunciation of a word has been shown to help children remember the meanings of words. The present study addressed whether the presence of a target word in Braille during instruction facilitated vocabulary learning more efficiently than an auditory-only instructional condition. The authors used an adapted alternating treatments single-case experimental design with three students with visual impairments who read Braille, collecting data on definition recall and spelling during each session. Data on definition recall were used to determine mastery. The results of this study are not consistent with previous findings with students who read print. Visual analyses of the data indicated that participants reached mastery in both conditions, but all three reached mastery on definition recall in fewer sessions in the auditory-only condition. Spellings of words were learned in the flashcard condition only, and possible implications of this are discussed. The difference in the unit of recognition and working memory load between reading Braille and reading print is discussed as one possible explanation.